Cohort profile: the Canadian coordination and activity tracking in children (CATCH) longitudinal cohort. Issue 9 (8th September 2019) - Cairney, John; Veldhuizen, Scott; Rodriguez, M Christine; King-Dowling, Sara; Kwan, Matthew Y; Wade, Terrance; Price, David; Missiuna, Cheryl; Timmons, Brian
Abstract : Purpose: Developmental coordination disorder (DCD) is a prevalent, neurodevelopmental disorder affecting 2% to 5% of children, which is characterised by fine and gross motor problems. Children with DCD have been shown to be less fit and physically active than other children; however, the direction of causality is unknown as previous studies have typically been done in older children when the differences in fitness and physical activity are already present. The aim of the Coordination and Activity Tracking in Children (CATCH) study is to specifically address the issue of precedence by recruiting a large sample of children in early childhood. Participants: CATCH comprises a community-based sample of parents and children 4 to 5 years of age divided into two groups: at risk for DCD (rDCD; n=287) and typically developing (TD; n=301). Inclusion in the rDCD group required a score at or below the 16 th percentile on a standardised test of motor coordination and a score above 70 on a standardised test of intelligence. Findings to date: Children in the rDCD group contained a higher proportion of males (67% vs 48%, χ 2 =21.9, p<0.001). Children in the rDCD group had lower mean IQs, aerobic and musculoskeletal fitness than children in the TD group (p<0.001 for all). There were no differences observed between groups for body composition or physical activity. Parent characteristics did not differ, with one exception: partners of reporting parents of rDCD children were less likely to hold a university degree (44% vs 57%, χ 2 =7.4, p=0.004). According to parent report, rDCD children experienced more problems in self-care, school and leisure activities (p<0.001 for all). Future plans: Children are being followed up annually for 3 years. At each follow-up, motor coordination testing is repeated, and data are collected on physical activity, fitness and social-emotional problems.